THE EFFECT OF NOVEL PACKAGING CONTAINING PHASE CHANGE MATERIAL ON BROCCOLI QUALITY DURING STORAGE - FAHIMEH VAHABI; SEPIDEH BAHRAMI; MARYAM MOSLEHISHAD (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Farmers and distributors find it challenging to maintain broccoli as a fresh vegetable during shelf life. Novel packaging can be used to extend the shelf life and preserve the nutritional value of the plant. Innovative aspects of this package include the use of high latent heat phase change materials, such as short chain paraffins in the polymer matrix. The weight loss, DPPH radical scavenging activity, glucosinolates, total phenol and moisture content, texture, color and microbiological test, have been investigated for 15 days by 5 days’ interval of storage under refrigerator temperature using PE packages containing phase change material and PVC packaging with ozone pretreatment. According to the results, the sample was packaged in PE containing phase change material during 15 days of storage had the lowest microbial count and the least amount of weight loss, the highest total phenol content and the highest content of glucosinolates. During 15 days of storage, the samples treated with 1.6 ppm ozone and the novel packaging showed more freshness and crispness. In comparison to the control sample, the L, a, and b indicators changed the least in the sample packed in novel packaging. Therefore, broccoli's shelf life can be successfully extended by using novel packaging with better preservation of its durability, sensory properties, and nutritional value and freshness of the agricultural product.